2018
DOI: 10.17305/bjbms.2018.2552
|View full text |Cite
|
Sign up to set email alerts
|

Control of body temperature and immune function in patients undergoing open surgery for gastric cancer

Abstract: The influence of mild perioperative hypothermia on the immune function and incidence of postoperative wound infections has been suggested, but the specific mechanism is unclear. This study aimed to analyze the body temperature, immune function, and wound infection rates in patients receiving open surgery for gastric cancer. Body temperature was controlled in each patient using one of four different methods: wrapping limbs, head and neck; insulated blankets; warming infusion fluids and insulated blankets; and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…[ 22 ] It has been shown that activation of the TGF-β signaling pathway is regulated by temperature. [ 23 , 24 ] Consistent with these findings, we found that that the serum level of TGF-β was higher in the 38°C group than in the 32 and 43°C groups. This may be because 38°C, the temperature closest to a child's physiologic temperature, resulted in balanced metabolism, which promoted the activation of TGF-β.…”
Section: Discussionsupporting
confidence: 85%
“…[ 22 ] It has been shown that activation of the TGF-β signaling pathway is regulated by temperature. [ 23 , 24 ] Consistent with these findings, we found that that the serum level of TGF-β was higher in the 38°C group than in the 32 and 43°C groups. This may be because 38°C, the temperature closest to a child's physiologic temperature, resulted in balanced metabolism, which promoted the activation of TGF-β.…”
Section: Discussionsupporting
confidence: 85%
“…Interoperative use of anaesthetic agents and intravenous solutions, especially multiple application of cold irrigation in debridement of open fractures, was due to low body temperature in anaesthetic‐surgical procedures. Hypothermia can lead to dysfunction of coagulation and contraction of vasculature around surgical site, this circumstance will compromise the immunity of tissue to pathogenic microorganism, and the underlying mechanism of low temperature affecting immune response has been reported . However, inadvertent intraoperative hypothermia is common but preventable adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…Alterações leves de temperatura podem resultar em desfechos desfavoráveis, sobretudo em cirurgias grandes, motivo pelo qual se configurem em um é um dos parâmetros fisiológicos que deve ser mais rigorosamente controlado. Segundo achados de um ensaio clínico chinês (18) , a variação da temperatura corporal durante o perioperatório afeta significativamente a função imunológica dos pacien-tes em um longo período pós-cirurgia, aumentando, assim, as chances de óbito.…”
Section: Discussionunclassified